O17.1 Histone deacetylase inhibitors alter the accumulation of cell-associated spliced hiv mrna – implications for reactivating the reservoir. (13th September 2015) - Mota, Talia M; Wightman, Fiona; Cheong, Karey; Lu, Hao K; Anderson, Jenny L; Purcell, Damian F; Lewin, Sharon
Abstract : Background: Clinical trials in HIV-infected patients on antiretroviral therapy with histone deacetylase inhibitors (HDACi) have demonstrated an increase in cell-associated unspliced (CA-US) HIV RNA, variable changes in plasma HIV RNA and no change in the number of latently infected cells. We aimed to define the effects of latency reversing agents (LRAs) on HIV mRNA splicing. Methods: Resting CD4 + T cells isolated from the blood of HIV-negative individuals were treated with the chemokine CCL19 and infected with wild type HIV NL4.3 to establish latency (n = 9). Latently infected CCL19-stimulated cells were then cultured with vorinostat, romidepsin, JQ1, romidepsin+JQ1 or PMA/PHA, all in the presence of an integrase inhibitor (L8). Cells and supernatant were harvested at 6, 24, 48, and 72 h. Reverse transcriptase (RT) was quantified in supernatant and CA-US and multiply spliced (MS) HIV RNA were quantified by real time qPCR. Results: In latently infected CCL19-treated CD4 + T-cells, stimulation with PMA/PHA led to a significant exponential increase in both US-RNA and MS-RNA by 72 h and reached a mean fold increase above baseline of 34-fold for US-RNA and 54-fold for MS-RNA (p = 0.0003, p = 0.0005 respectively, relative to DMSO). In contrast, following stimulation with each LRA, there was only a modest increase in CA-US RNA that was not statistically significantly different from DMSO (p = 0.89). MS-RNA increased transiently (mean 1.65-fold change at 6hr with romidepsin) and then significantly declined over time with a reduction to 0.18-fold by 72 h relative to DMSO (p = 0.008 romidepsin compared to baseline) in the absence of any cellular cytotoxicity. Conclusions: In this in vitro model of latency, PMA/PHA and the potent HDACi romidepsin had strikingly different effects on the accumulation of US-RNA, MS-RNA and virus production. Changes in HIV RNA splicing may limit the efficacy of HDACi in activating latent HIV.